2014
DOI: 10.1093/ntr/ntu218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicant and Carcinogen Metabolites in the Urine of E-Cigarette Users Versus Cigarette Smokers

Abstract: With respect to the compounds analyzed here, e-cigarettes have a more favorable toxicity profile than tobacco cigarettes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
182
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(198 citation statements)
references
References 29 publications
15
182
1
Order By: Relevance
“…[8][9][10][11][12][13] Very little research on observed toxicant levels in e-cigarette users has been conducted. 14,15 To help better inform whether or not e-cigarettes pose real utility as a harm reduction device, data are needed to assess levels of nicotine, carcinogenic substances, and other toxicants in cigarette smokers who switch to e-cigarettes. In this longitudinal within-subjects observational study, we evaluated the effects of e-cigarettes on nicotine delivery and exposure reduction to selected carcinogens and toxicants.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Very little research on observed toxicant levels in e-cigarette users has been conducted. 14,15 To help better inform whether or not e-cigarettes pose real utility as a harm reduction device, data are needed to assess levels of nicotine, carcinogenic substances, and other toxicants in cigarette smokers who switch to e-cigarettes. In this longitudinal within-subjects observational study, we evaluated the effects of e-cigarettes on nicotine delivery and exposure reduction to selected carcinogens and toxicants.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Lower biomarker levels from toxicants associated with tobacco-related disease were observed in e-cigarette users. 4 From a technical perspective, the perception of the relative safety of e-cigarettes is based on their different mechanism of aerosol/vapor formation, compared with traditional combustible tobacco products. It is assumed that e-cigarettes do not generate many of the harmful and potentially harmful constituents (HPHCs 5 ) inherent to combustible tobacco smoke because unlike the traditional cigarette that burns the tobacco leafs the e-cigarette heats the vegetable glycerine, propylene glycol, and other components of e-liquids at a lower temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that acrolein levels in ENDS users, smokers who converted to ENDS use and smokers who entered dual use were much lower than in cigarette users. 24,25 Toxins and carcinogens Analysis of vapour and urine from ENDS user shows lower concentrations of hazardous toxins and carcinogens compared to cigarette users. 24,26 Comparing the presence and level of known harmful substances in ENDS and cigarettes, it has been estimated that ENDS are 95% less harmful.…”
Section: Aldehydesmentioning
confidence: 99%
“…24,25 Toxins and carcinogens Analysis of vapour and urine from ENDS user shows lower concentrations of hazardous toxins and carcinogens compared to cigarette users. 24,26 Comparing the presence and level of known harmful substances in ENDS and cigarettes, it has been estimated that ENDS are 95% less harmful. 27 However, it has been shown that toxin levels vary widely between different ENDS products.…”
Section: Aldehydesmentioning
confidence: 99%